Consanguinity And Pregnancy Outcome Among Rural Pregnant Women of Belgaum District - Metgud, Chandra S; Naik, Vijaya A; Mallapur, Maheshwar D (National Journal of Community Medicine, 2012)
Background: Although unions between close biological relatives are preferred in many parts of South India, there still is a large gap of knowledge of this feature of human kinship structure. So, the present study was conducted to know the prevalence and types of consanguineous marriages and its effect on abortion, stillbirth, mortality and congenital malformation. Methods: The present longitudinal study was carried out in Kinaye Primary Health Centre of district Belgaum. All the pregnant women residing in the study area were included in the study, the number of whom was 1138. Results: The prevalence of consanguinity in our study was found to be 20.3%. Majority (53.2%) of the marriages were between first cousins. The prevalence of consanguinity was significantly higher in illiterate couples (p < 0.001 and p 0.004) and in women belonging to Muslim religion (p 0.02). No significant effect of consanguinity was noted on the rate of abortion, stillbirth, mortality and congenital malformation. Conclusion: Consanguinity was higher among illiterate rural couples. Hence efforts should be made to enhance the literacy status through Information, Education and Communication activities. Consanguinity is one of the important contributory factors for adverse pregnancy outcomes. So, it would be advisable to avoid consanguineous unions in families where already a congenital malformed child has been born.